Oxidative stress markers in saliva and plasma differ between diet-controlled and insulin-controlled gestational diabetes mellitus. (February 2019) - Zygula, Aleksandra; Kosinski, Przemyslaw; Zwierzchowska, Aneta; Sochacka, Malgorzata; Wroczynski, Piotr; Makarewicz-Wujec, Magdalena; Pietrzak, Bronislawa; Wielgos, Mirosław; Rzentala, Mateusz; Giebultowicz, Joanna
Abstract: Objectives: The aims of the study were as follows: to investigate possible differences between plasma oxidative status (OS) in late-onset GDM and well-characterized healthy pregnant women (oral health, diet); to verify the existence of possible differences between GDMG1 (diet-treated) and GDMG2 (insulin-treated GDM); to determine whether oxidative stress markers could be detected in saliva. Material and methods: A total of 89 pregnant women ( n  = 89; 59 with GDM and 30 controls) were evaluated. Malondialdehyde (MDA), total antioxidant capacity (ORAC), inactivation of aldehyde dehydrogenase (IALDH ), activity of glutathione peroxidase (GPx) and glutathione transferase (GST)) in plasma and/or saliva were analyzed. Results: The activity of GPx and GST in plasma was higher in GDMG2 as compared to GDMG1 and controls. Also, in GDMG2, elevated concentrations of salivary MDA and higher IALDH were observed. In contrast, GDMG1 had higher plasma ORAC and lower GPx activity as compared to controls, probably due to low-energy diet, high in antioxidants and fibers. Salivary and plasma OS were correlated and most significant for ORAC. Conclusion: Oxidative stress were not observed in GDMG1 but were confirmed to be moderate in GDMG2. However, large variability of the analyzed markers in GDM groups encourages screening of all patients, regardless of the treatment option. Saliva may be considered useful for the estimation of oxidative stress levels in GDM populations